What interventions should we implement in England's mental health services? The mental health implementation network (MHIN) mixed-methods approach to rapid prioritisation - Ahuja, Shalini; Phillips, Lawrence; Smartt, Caroline; Khalid, Sundus; Coldham, Tina; Fischer, Laura; Rae, Sarah; Sevdalis, Nick; Boaz, Annette; Robinson, Sarah; Gaughran, Fiona; Lelliott, Zoe; et al. (Frontiers in Health Services, 2023)
Introduction Setting mental health priorities helps researchers, policy makers, and service funders improve mental health services. In the context of a national mental health implementation programme in England, this study aims to identify implementable evidence-based interventions in key priority areas to improve mental health service delivery. Methods A mixed-methods research design was used for a three step prioritisation approach involving systematic scoping reviews (additional manuscript under development), expert consultations and data triangulation. Groups with diverse expertise, including experts by experience, worked together to improve decision-making quality by promoting more inclusive and comprehensive discussions. A multi-criteria decision analysis (MCDA) model was used to combine participants' varied opinions, data and judgments about the data's relevance to the issues at hand during a decision conferencing workshop where the priorities were finalised. Results The study identified mental health interventions in three mental health priority areas: mental health inequalities, child and adolescent mental health, comorbidities with a focus on integration of mental and physical health services and mental health and substance misuse problems. Key interventions in all the priority areas are outlined. The programme is putting some of these evidence-based interventions into action nationwide in each of these three priority mental health priority areas. Conclusion We report an inclusive attempt to ensure that the list of mental health service priorities agrees with perceived needs on the ground and focuses on evidence-based interventions. Other fields of healthcare may also benefit from this methodological approach if they need to make rapid health-prioritisation decisions.